Immanence and Autobiography: Gilles Deleuze’s a Life and Sarah Kofman’s Autobiogriffure - Tan, Jean Emily P (Archīum Ateneo, 2020)
How does the “I” of autobiography relate to the “I” of the philosopher? Is there an alternative to conceiving of this relation in terms of the opposition between the particular to the universal? This essay offers Deleuze’s notion of immanence as a fruitful way of approaching this question by staging an encounter between Sarah Kofman’s autobiographical work, Rue Ordener, Rue Labat, and Gilles Deleuze’s “Immanence: A Life.” In this textual encounter, Kofman’s autobiography is interpreted in light of Deleuze’s concept of “immanence” and Deleuze’s notion of “a life” is explicated through its application to autobiography.